ABOUT YIELDS AT FLAME AND ELECTRICAL FURNACES USED IN THE TECHNOLOGICAL OPERATIONS OF THE HEAT TREATMENTS - Alin Stancioiu (Fiabilitate şi Durabilitate)
It should be taken into account a number of factors, such as: technical treatment type (temperature), shape and size of the piece, manufacturing series etc. The difficulty costing in that the same heat treatment can be performed in different furnaces and the same furnaces may be used for further heat treatment. The optimal solution can establish only after some comparative assessment of different types of furnaces, taking into account the constructive particularities and technical and economic parameters